Histopathological Analysis of Liver Damage in Rasbora lateristriata Fish Induced by Extract Butterfly Pea Flower (Clitoria ternatea) - Pertiwi, Anggita Endar; Illiyin, Sirayya; Sadewo, Imran; Rahayu, Sekar; Rumansara, Papuani Samparisna; Podhi, Felisitas Moli; Sularsah, Sais; Adelfiani, Adelfiani; Retnoaji, Bambang; Sofyantoro, Fajar; Nuriliani, Ardaning; Wijayanti, Nastiti; Saragih, Hendry T. S. S. G.; Rohmah, Zuliyati; Widiyanto, Slamet; Empra, Desi Eka Putri; Ariesti, Wiwin; Septriani, Nur Indah (Universitas Pattimura, 2026)
Butterfly pea flower (Clitoria ternatea) is an Indonesian native plant known for its medicinal properties due to its rich content of anthocyanins, flavonoids, and ternatins. Although widely recognized for its health benefits, the long-term effects of its bioactive compounds require careful evaluation. This study aimed to investigate the potential hepatotoxic effects of butterfly pea flower extract on the liver of Rasbora lateristriata fish. Fish were exposed to 0 (control), 50, 75, and 100 ppm of butterfly pea extract for four days, with four fish allocated per group. Histological markers, including necrosis, vacuolization, pyknosis, and hemorrhage, were assessed in liver tissues. Data were analyzed using the Kruskal-Wallis test and Mann-Whitney U test at a 95% confidence level. Results indicated that butterfly pea flower extract caused significant hepatic damage, with increased severity at higher concentrations. The most pronounced damage was observed at 75 ppm, suggesting an optimal dose for inducing oxidative stress. This study highlights the potential hepatotoxicity of butterfly pea flower extract in aquatic species and underscores the need for further research to evaluate its safety for therapeutic use.